Nitroglycerin-induced downregulation of AKT- and ERK1/2-mediated radiation-sensitive 52 expression to enhance pemetrexed-induced cytotoxicity in human lung cancer cells. Issue 2 (26th March 2022) - Ko, Jen-Chung; Chen, Jyh-Cheng; Tseng, Pei-Yu; Hsieh, Jou-Min; Chiang, Chen-Shan; Liu, Li-Ling; Chien, Chin-Cheng; Huang, I-Hsiang; Lin, Yun-Wei
Abstract: Nitroglycerin (NTG)—a nitric oxide–donating drug—is traditionally administered via the sublingual route to treat acute myocardial angina attacks. NTG also increases tumor blood flow and, consequently, cancer drug delivery to tumor cells. In the homologous recombination pathway, radiation-sensitive 52 (Rad52) plays a crucial role in DNA repair by promoting the annealing of complementary single-stranded DNA and stimulating radiation-sensitive 51 (Rad51) recombinase activity. Pemetrexed—a multitargeted antifolate agent—exhibits satisfactory clinical activity in wild-type nonsquamous non-small-cell lung cancer (NSCLC) cells. However, the synergistic activity of combination therapy with NTG and pemetrexed against NSCLC cells has not yet been clarified. In 2 NSCLC cell lines (i.e. lung squamous cell carcinoma H520 and lung adenocarcinoma H1975 cells), NTG reduced Rad52 expression; in addition, decreased phospho-AKT and phospho-ERK1/2 protein levels were observed. Enhancement of AKT or ERK1/2 activity through transfection with a constitutively active AKT (AKT-CA) vector or constitutively active mitogen-activated protein kinase kinase 1 (MKK1-CA) vector increased the Rad52 protein level and cell survival, which were suppressed by NTG. The knockdown of Rad52 expression by using small interfering RNA or by inhibiting AKT and ERK1/2 activity enhanced the cytotoxicity and cell growth inhibition induced by NTG. Moreover, NTG synergistically enhanced the cytotoxicity and cell growth inhibition induced by pemetrexed in NSCLC cells; these effects were associated with AKT and ERK1/2 inactivation and, consequently, Rad52 downregulation in H520 and H1975 cells. The results provide a rationale for combining NTG and pemetrexed in lung cancer treatment to improve lung cancer control.